Carpal Tunnel Syndrome Prevalence and Characteristics among Administrative Staff at Dr.Hasan Sadikin General Hospital Bandung - Andrian, Andrian; Lailiyya, Nushrotul; Novitri, Novitri (Althea Medical Journal, 2017)
Background: Carpal tunnel syndrome (CTS) is a neurologic disease affecting hands, which is closely related to work, and is the most prevalent nerve compression disease. The incidence of CTS quite often occur in people working with their hands, for instance the administrative staff, especially in a busy workplace such as Dr.Hasan Sadikin General Hospital Bandung. CTS causes reduction in work productivity, and consequently degrading family welfare and the quality of public service. For that very reason, the prevalence and characteristics of CTS among administrative staff at Dr.HasanSadikin General Hospital Bandung needed to be revealed.Methods: This quantitative descriptive study involved 94 administrative staff in the Medical record department of Dr. Hasan Sadikin General Hospital using the Carpal-tunnel.net questionnaire and further examinations by neurologists. Variables involved in this study were the subject characteristics.Results: Out of the 90 subjects, 22 stated having symptoms related to CTS (prevalence, 24.4%). On further clinical examination, 3 were diagnosed of suffering from CTS (prevalence, 3.3%).Conclusions: Carpal tunnel syndrome is found among the administrative staff at Dr. Hasan Sadikin General Hospital BandungÂ and the prevalence is lower than in the general population. A further study is required to reveal ther specific division in the hospital with the most prevalent CTS case.DOI:Â 10.15850/amj.v4n2.1077